Moon mission : the epic 400-year journey to Apollo 11 - Brouwer, Sigmund, 1959- (Kids Can Press, 2019)
Looks at over 400 years of science, technology, engineering, and math that evolved to the point where in 1969, humans were able to walk on the moon. Walks readers through the Apollo 11 mission from take off to landing and the various near-catastrophic challenges that almost meant the failure of the mission. Includes "Solve the Mystery" sidebars that highlight major discoveries and innovations.